Efficacies of Sordarin Derivatives GM193663, GM211676, and GM237354 in a Murine Model of Systemic Coccidioidomycosis - Clemons, Karl V. (American Society for Microbiology, 2000)
Sordarin derivatives (Glaxo Wellcome) are a new class of compounds that selectively inhibit fungal protein synthesis and have a broad spectrum of activity. Systemic coccidioidomycosis was established in female CD-1 mice infected with Coccidioides immitis, and therapy was begun on day 4 with either GM193663, GM211676, GM237354, fluconazole, or no treatment; compounds were given twice daily orally for 19 days at 20 or 100 mg/kg/day. The serum pharmacokinetics of the compounds were studied in uninfected mice. The MICs of GM193663, GM211676, and GM237354 for C. immitis were 1.56, 0.39, and 0.39 μg/ml, respectively, and the minimum fungicidal concentrations were 6.25, 3.13, and 0.39 μg/ml, respectively. Peak serum levels (sampled at 1 to 2 h) after a single 50-mg/kg dose were 9.8 μg/ml for GM193663, 13 μg/ml for GM211676, and 6.0 μg/ml for GM237354. No accumulation occurred after 19 days of dosing, and peak levels were lower at 3.2 μg/ml for GM193663, 4.0 μg/ml for GM211676, and <2.5 μg/ml for GM237354. We estimate that the t(1/2) for each compound in serum is <2 h. In vivo, all compounds showed dose-responsive efficacy, significantly prolonging survival over the control groups (100% lethal dose); 80 to 100% of the mice given the 100-mg/kg doses of fluconazole or a GM drug survived. All 100-mg/kg/day regimens were equivalent. At 20 mg/kg/day, GM211676 was equivalent to 100 mg of fluconazole/kg/day, indicating that GM211676 was ∼5-fold more efficacious. No mice surviving the 49 days of the experiment were free of infection. All drugs dose responsively reduced the fungal burden in the spleen, liver, and lungs, and GM237354 at 100 mg/kg/day was superior to all of the other regimens in the reduction of burden in all organs. C. immitis was susceptible both in vitro and in vivo to the GM compounds, which were found to be equivalent or superior to fluconazole. These results are encouraging, indicating that further testing in other models of fungal disease is warranted.